The New Luxembourg Insolvency and Restructuring Law in Light of the Transposition of the Directive (EU) 2019/1023 - Mastrullo, Thomas (European Insolvency and Restructuring Journal, 2024)
The transposition of the Directive (EU) 2019/1023 by the Law of 7 August 2023 has provided an opportunity to update Luxembourg’s insolvency and restructuring law, addressing aspects such as insolvency prevention, debt and business restructuring, the second chance for honest insolvent entrepreneurs, and the effectiveness of insolvency proceedings. New proceedings, new practitioners and new mechanisms have been introduced into Luxembourg law.While the new rules require adaptation and may be subject to discussion on certain points, the transposition of the Directive (EU) 2019/1023 aligns Luxembourg law with European standards in the realm of restructuring and insolvency. Consequently, this move enhances its competitiveness.